T cell-mediated immune surveillance conferred by latent Epstein-Barr virus genes suppresses a broad spectrum of tumor formation through NKG2D-NKG2DL interactions - Jin, Yuqi; Guo, Yun; Kawano, Yohei; Sasatani, Megumi; Ohki, Shun; Yamane, Keita; Ota, Yusei; Tamura, Yumi; Sotomaru, Yusuke; Baba, Yoshihiro; Yasuda, Tomoharu (Frontiers in Immunology, 2025)
Epstein-Barr virus (EBV)-infected B cells effectively induce T cell-mediated immune surveillance that suppresses the proliferation of EBV+ B cells and development of lymphomas. However, it remains unclear whether EBV-specific T cells are involved in the surveillance of EBV-negative general tumors. To address this issue, we induced immune surveillance by expressing key EBV antigens, LMP1 and LMP2A, in germinal center B cells and investigated the formation of non-B cell tumors. LMP1/2A mice showed a significantly reduced incidence of radiation-induced T-cell acute lymphoblastic leukemia/lymphoma (T-ALL) even in the absence of LMP antigens in tumor cells and an extended life-span compared to control mice. LMP1/2A mice showed significantly higher numbers of activated memory T cells in both CD4+ and CD8+ αβT cell fractions compared to controls, suggesting their role in the elimination of tumor cells. Despite nearly absent MHC class I expression, tumor cells were effectively killed by CD8+ T cells activated upon LMP1/2A-expressing B cells. Transcriptome analysis identified upregulation of the NKG2D-NKG2DL pathway, emphasizing the capacity of LMP1/2A-induced T cells in the recognition of common tumor specific antigens. Moreover, not only T-cell tumors, but also intestinal tumors caused by ApcMin mutation were significantly suppressed by the LMP1/2A-induced immune surveillance. These results suggest that LMP1/2A-expression associated with EBV infection contributes to pan-tumor surveillance, implicating a beneficial aspect of EBV infection in humans and providing important insights into cancer prevention.